Representações sociais de professoras tecidas em colcha de retalhos e caderno de memórias - Cardoso, Soraia Souza (2017)
The purpose of this research is to carry out a study on the social representations of narratives and paintings about the literacy period of a group of teachers working for São Paulo capital state. In one of the continuous education meetings, these women elicited the imaginary world belonging to this stage of childhood which they work with their pupils. The longed-for memories of this child life moment were painted in pieces of fabric and, when sewn, they resulted in a Patchwork Quilt that is stitched together with collective knowledge and experiences. The Patchwork Quilt is comprehended as an account of relations woven by life stories that are loaded with feelings and emotions stored long ago. The written narratives that compose the Book of Memories also brought to the light this Imaginary World: another thread of the fabric that is attached to the remaining cluster highlighted by the Social Representations. In other words, it is a way of tracking, from different angles, the vestiges of meaning’s origin revealed by this group of teachers, trying to establish relations between social and individual factors. Understanding the images of the Patchwork Quilt and the narratives of the Book of Memories consisted of a confluence movement with what we have experienced and what we are. It unravels in a cyclical and self-educating process, in which the complexity of each patch, along with the singular and amalgamated narratives, is achieved in the consistent whole of this research